Nonprofit internet strategies : best practices for marketing, communications, and fundraising success - Hart, Ted, 1964-; Greenfield, James M., 1936-; Johnston, Michael W., 1963- (Wiley, 2005)
Nonprofit Internet Strategies offers every charitable organization the opportunity to analyze their options and select the appropriate strategy to integrate traditional marketing, communications, and fundraising practices with their online efforts. It is an excellent how-to guide--a practical manual for nonprofit staff written in non-technical language--prepared by experts in the field based on real-life experiences and case studies.